MODELLING THE FACTORS AFFECTING FINANCIAL LITERACY OF WOMEN TOWARDS DIGITAL PAYMENTS USING ISM AND MICMAC APPROACH (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
In today’s ever-changing technological era, the  innovative and improvising advancements has  facilitated the digital payments progressively and  has become the most prominent constituent of  financial literacy in the midst of the women’s  society. This study aims at determining the  factors which affects the level of financial  literacy of women towards digital payments.  The ten selected influencing factors of women’s  financial literacy are identified from the study  of literature. Interpretive Structural Modelling  (ISM) and MIC-MAC approach has been  applied to test how one factor’s impact the other  influencing factor. The outcomes of the study  makes the valuable contribution to researchers  in the terrain of behavioural finance and  advancement of technical era as well as growth  of financial literacy.
Keywords: Digital payments; ISM model; MICMAC approach; women’s financial literacy